The Islamic State: a comparative history of jihadist warfare - Celso, Anthony N. (Lexington Books, 2018)
The book examines the progressive radicalization of modern Sunni jihadist movements from a comparative perspective. It links growing jihadist extremism to past failures and analyzes the rise and fall of the Islamic State's "caliphate" as the culmination of this evolution